(untitled) (INNOVATIVE ECONOMY, 2020)
Zelinska O.Z. CONCEPTUAL APPROACHES TO IMPROVING THE FOREIGN ECONOMIC ACTIVITY OF THE REGION IN THE CONTEXT OF EURO-REGIONAL COOPERATION Purpose. The aim of the study is development and harmonization of conceptual approaches to the improvement of normative and legal, organizational and economic mechanisms of development of foreign economic activity in the conditions of Euro-regional cooperation. Methodology of research. A set of general scientific research methods is used to achieve the defined goal and objectives, thanks to which the scientific literature and normative-legislative documents on the topic of scientific research are generalized. Thus, comparison methods are used to identify differences and find common features in the concepts of “cross-border” and “Euro-regional” cooperation; methods of generalization and abstraction to substantiate the concepts of “intensification of foreign economic activity of the region” and “organizational and economic mechanism of intensification of foreign economic activity of the region in terms of Euro-regional cooperation”. The system approach allowed to explore the essence of the concept of “foreign economic activity of the region”, namely its patterns, mechanisms, forms, types and directions, one of which is cross-border (Euro-regional) cooperation. Methods of classification (typology) are revealed for systematization of the factors having essential influence on development of foreign economic activity of regions in the conditions of Euro-regional cooperation. Findings. The main reasons for the low development of foreign economic activity of the regions of Ukraine are identified, which are primarily: the imperfection of the regulatory and legislative system of state regulation of foreign economic activity in the region; raw material nature of products of domestic enterprises, which has low competitiveness; difficult economic situation related to the global Covid-19 pandemic, which is accompanied by negative social and economic phenomena, etc. The main directions of intensification of foreign economic activity of the region in the conditions of strengthening of Euro-regional cooperation as one of priority preconditions of active development of innovative enterprises, which determines competitive advantages in the world market of goods and services, are substantiated. The own definition of such concepts as: “Euro-regional cooperation”, “intensification of foreign economic activity in the conditions of Euro-regional cooperation”, “organizational and economic mechanism of activization of foreign economic activity of the region in the conditions of Euro-regional cooperation” is formulated. It is determined that the intensification of foreign economic activity of the region in the field of Euro-regional cooperation allows to achieve stable and balanced development of international cooperation, develop mechanisms to ensure management of the entire system of interregional relations, integrate into the European space, which is especially important for Ukraine. Originality. For the first time, the concept of “intensification of foreign economic activity” in the context of Euro-regional cooperation as a set of organizational, legal and technical measures aimed at integrating the economy of Euro-regional entities into the new world economic space, including deepening international relations with EU countries. At the same time, in contrast to the existing one, the strategic guidelines for intensifying the foreign economic activity of the region in the field of Euro-regional cooperation are grouped in separate areas: organizational and institutional; organizational and legal; organizational, economic and financial. Practical value. The results of the research can be implemented in the activities of local and regional government in terms of intensification of foreign economic activity of the regions and Euro-regional cooperation, which will contribute to the processes of Ukraine’s entry into the world economy. Key words: foreign economic activity, Euro-regional cooperation, activation, Euro-region, Euro-regional formation.